แบบจำลองการชกหมัดตรงที่ทรงประสิทธิภาพในกีฬามวย - รัตน์ ทองเอี่ยม (จุฬาลงกรณ์มหาวิทยาลัย, 2016)
Rear hand straight punch (RHSP) is a punch used for scoring or for maximum power with high speed and accuracy. Hence, the understanding of biomechanics aspect of RHSP helps improve efficiency of boxers and their punches. The objective of this research is, thus, to explain the mechanics of RHSP through a biomechanical model. The research had two parts The first study dealt with phasing of RHSP in boxers. Three boxers were recruited and punched at a punching ball located at the level of the boxers’ head. 3-D kinematic and ground reaction force (GRF) were collected. The collected data was then analyzed to find the phase of punch using the pattern of GRF as criteria. The results found that RHSP had 3 phases. The first phase began with boxers shifting their weight to the rear leg. At this phase, the GRF of the rear leg increased. The first phase ended when boxers completely lifted their lead leg. At this point, the GRF of the lead leg equaled to zero. The first phase was called "lead foot off" (LFO). The second phase happed when the boxers began to shift themselves forward. The second phase started when the boxers completely lifted their fore leg off the ground until it began to bear weight again. The second phase was called "lead foot in" (LFI). The final phase happened when the boxers threw their punch to the target. At this phase, the lead leg of boxers bore weight and acted as a support. The final phase ended when the punch hit the target. The kinetic chain of the punch started from knee, hip, shoulder, elbow, and fist. From the result, participant T2 had maximum punch velocity of 6.63 m/s with an X-factor angle of 53.30 degrees at the target and had the widest X-factor of 43.21 degrees. The second study developed a biomechanical model to explain the mechanics of RHSP. Five boxers were recruited in the study. The participants punched a sandbag at the height equivalent to the height of their head. 3-D kinematic data and GRF were collected. The results showed that participant B5 hit the target with highest punch force to body weight ratio. Therefore, the biomechanical model was constructed from the punch of participant B5 where inverse and forward dynamic models were created using LifeMODTM software. After the forward dynamic model was created, it was used to maximize the punching force of the boxer. The result showed that the model could create a maximum punch force of 1861 N which was a 32.27% increase. From the motion agents, the results showed that the punch velocity was 7.11 m/s (an increase of 16.59%). The maximum linear velocities of center of mass on sagittal plane of upper arm, lower arm, and fist was 5.57 m/s (+7.60%), 7.94 m/s (+4.52%) and 8.98 m/s (+1.84%), respectively. The maximum angular velocities of center of mass on transverse plane of upper body (Thoracic), middle body (Lumbar), and lower body (Pelvic) were 804.48 deg/s (+5.60%), 592.91 deg/s (+4.52%), and 457.752 deg/s (+5.37%) respectively. The results showed that punch force started when boxers shifted their bodyweight to rear leg until the lead leg bore no bodyweight. While the boxers shifted bodyweight to their rear leg, the boxers turned their body toward the rear leg. After that, the boxers shifted their bodyweight back to lead leg until the lead leg bore bodyweight. At that point, the hip of the lead leg acted as a fulcrum for the body to twist to the direction of lead leg to develop velocity and transfer force from lower extremity to upper extremity. The velocity and force transferred threw punch to the target. As a result, core muscle was very important in bridging the force transition from lower extremity to upper extremity. Creating high velocity punch resulted in high impact punch. To create high impact punch, boxers and coaches should focus on increasing velocity of body twist from lower body to upper body and increase punch speed. The muscle group that involved in RHSP included hip flexor, rotator adductor of lead side as well as torso rotator.